Deep Learning for Image-Recognition-Based Cassava Disease Detection - CGIAR Platform for Big Data in Agriculture (2019)
We trained a convolutional neural network on a cassava image database to identify three diseases and two types of pest damage: brown leaf spot, red mite damage, green mite damage, brown streak disease, and cassava mosaic disease. Results show that image recognition is an easily deployable strategy for disease detection.